(Almost) Lost at SEA: An Unusual Cause of Cortical Blindness. (2nd January 2017) - Walden, Jeffrey; Van Williamson, Edward
ABSTRACT: A middle-aged man with a history of type 2 diabetes mellitus, hypertension, hyperlipidemia, prior cerebral vascular accident, and remote history of generalized seizure disorder presented with worsening right-sided visual deficits and focal seizures. On examination the patient had dense homonymous hemianopsia on the right side. He was initially diagnosed with a stroke and underwent further investigation for potential causes. However, upon further review, magnetic resonance imaging (MRI) findings and repeat examination were more consistent with seizure-related effects on cortical brain matter as the cause of his visual disturbances rather than stroke. An EEG confirmed focal seizures from the left posterior quadrant of the brain, and the diagnosis of status epilepticus amauroticus (SEA) was made. The hemianopsia resolved with antiepileptic treatment.